The railway metropolis : how planners, politicians and developers shaped modern London - Schabas, Michael (ICE Publishing, 2016)
'The Railway Metropolis' describes the story of how planners, politicians and developers have shaped London's railways. Focusing on the new lines that have been added since 1980 the author considers the reasons why they were built, whether they have proved worthwhile and what lessons can be learned.